Treatment of hypotrichosis simplex of the scalp with the combination of botanic extracts and minoxidil: a case report - Zhuang, Mingyue; Xu, Yonglong; Zhong, Shiyi; Tian, Ziyuan; Liu, Qingwu; Yang, Dingquan (Frontiers in Genetics, 2025)
Hypotrichosis simplex of the scalp (HSS) is a clinically rare monogenic autosomal dominant disorder associated with variants in the gene CDSN, which encodes the desmosome protein corneodesmosin. Although studies have reported that some medications can improve the symptoms of hair loss in HSS, there is still a lack of definitive and effective treatments for this disease. We report a familial case of HSS in an 8-year-old male child diagnosed with HSS caused by a mutation in CDSN, who was treated with botanical extracts in combination with minoxidil, which resulted in significant hair growth after two treatments. This is the first study describing the improvement of clinical symptoms of HSS with oral botanical extracts. This suggests that botanical extracts in combination with minoxidil may be a therapeutic approach for HSS in the clinic.